أهمية تواجد المختص النفسي في المدارس الابتدائية - بوبكر,نجاة; قريدة,يحي (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية إلى التعرف على أهمية تواجد المختص النفسي في المدارس الابتدائية من وجهة نظر أساتذة التعليم الابتدائي، كما هدفت الى التعرف على دلالة الفروق بين الجنسين في اتجاهات أساتذة التعليم الابتدائي نحو أهمية تواجد المختص النفسي في المدارس الابتدائية ، وهدفت أيضا إلى التعرف على دلالة الفروق في الخبرة في اتجاهات أساتذة التعليم الابتدائي نحو أهمية تواجد المختص النفسي في المدارس الابتدائية. ولهذا الغرض اعتمدنا على عينةمكونة من(104)أستاذا، منهم( 37 )ذكور و (67 )إناث من أساتذة التعليم الابتدائي بولاية توقرت . وقد اعتمد الباحثان المنهج الوصفي المناسب للدراسة، كما تبنيا استبيان معد مسبقا .واستخدمنا الأسلوب الإحصائي اختبار T .Test)) لدلالة الفروق بين متوسطي مجموعتين. وقد أسفرت النتائج على ما يلي: *اتجاهات أساتذة التعليم الابتدائي إيجابية نحو أهمية تواجد المختص النفسي في المدارس الابتدائية. *عدم وجود فروق دالة إحصائيا بين اتجاهات أساتذة التعليم الابتدائي نحو أهمية تواجد المختص النفسي في المدارس الابتدائية تعزى لمتغير الجنس. *عدم وجود فروق دالة إحصائيا بين اتجاهات أساتذة التعليم الابتدائي نحو أهمية تواجد المختص النفسي في المدارس الابتدائية تعزى لمتغير الخبرة المهنية. The current study aimed to identify the importance of the presence of a psychological specialist in primary schools from the point of view of primary school teachers, It also aimed to identify the significance of gender differences in the attitudes| education of primary school teachers the importance of the presence of a psychological specialist in primary school, it also aimed to identify the significance of differences in experience in the attitudes of primary school teachers towards the importance of presence of a psychologist in primary schools. For this purpose, we relied on a sample of (104) professors, including (37) males and (67) females in the state of touggourt. The researchers adopted the appropriate descriptive approach for the study, and Adopted a preــ prepared questionnaire, we used the Statistical method (TــTest) to indicate the differences between the average of two groups. The results showed the following: *primary school teachers’ attitudes are positivetowards the importanceof the presence of a psychologist in primary schools *Differences between the attitudes of primary school teacherstowards the importanceof the presence of a psychologist in primaryschools due to the gendervariable * the importance of the presence of a psychologist specialist in there are no statistically significant differences between the attitudes of primary school teachers, Primary schools areattributed to the variable ofprofessional experience towards.
من وجهة نظر أساتذة التعليم الابتدائي